Structural variability in M2+ 2-hydroxyphosphonoacetate moderate proton conductors - Pérez-Colodrero, Rosario Mercedes; Salcedo, Inés R.; Bazaga-García, Montse; Milla-Pérez, Diego F.; Durán-Martín, Jonatan D.; Ramírez-Losilla, Enrique; Moreno-Real, Laureano; Rius, Jordi; García-Aranda, Miguel Ángel; Demadis, Konstantinos D.; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio (De Gruyter, 2017)
The structural variability of two series of Mg2+- and Zn2+- 2-hydroxyphosphonoacetates have been studied in the range of 25–80 °C and 95 % relative humidity in order to correlate the structure with the proton conductivity properties. In addition to selected previously reported 1D, 2D and 3D materials, a new compound, KZn6(OOCCH(OH)PO3)4(OH)·5H2O (KZn6-HPAA-3D), has been prepared and thoroughly characterized. The crystal structure of this solid, solved ab initio from synchrotron X-ray powder diffraction data, consists of a negatively charged 3D framework with K+ ions, as compensating counterions. It also contains water molecules filling the cavities in contrast to the potassium-free 3D anhydrous NH4Zn(OOCCH(OH)PO3) (NH4Zn-HPAA-3D). In the range of temperature studied, the 1D materials exhibit a 1D → 2D solid-state transition. At 80 °C and 95 % RH, the 2D solids show moderate proton conductivities, between 2.1 × 10 − 5 S·cm − 1 and 6.7 × 10− 5 S·cm− 1. The proton conductivity is slightly increased by ammonia adsorption up to 2.6 × 10 − 4 S·cm − 1, although no ammonia intercalation was observed. As synthesized KZn6-HPAA-3D exhibits a low proton conductivity, 1.6 × 10− 6 S·cm− 1, attributed to the basic character of the framework and a low mobility of water molecules. However, this solid transforms to the 2D phase, Zn(OOCCH(OH)PO3H)·2H2O, upon exposure to dry HCl(g), which enhances the proton conductivity with respect to the as-synthesized 2D material (4.5 × 10− 4 S·cm− 1). On the other hand, NH4Zn-HPAA-3D exhibited a higher proton conductivity, 1.4 × 10− 4 S·cm− 1, than the K+ analog.
Keywords: Conductividad eléctrica; Semimetales; Polímeros organometálicos; Química del estado sólido; POC-16; Coordination polymers; Metal phosphonates; Proton-conductivity; Solid-state chemistry